Prevalence of Sexually Transmitted Infections in the United Kingdom from Home-Collected Samples: A Cross-Sectional Laboratory Analysis of over 6000 Cases - Mary, Jo Kurth; Joanne, Watt; Katie, Coyle; Laura, Mooney; Gary, Smyth; John, V. Lamont; Peter, Fitzgerald; Mark, W. Ruddock (International Journal of Sexually Transmitted Diseases, 2026)
Background Sexually transmitted infections (STIs) continue to rise globally, with >1 million new cases reported daily in 2020. In England, newly diagnosed STIs increased by 23.8% in 2022 compared to 2021. Many infections remain asymptomatic yet contribute to infertility, pregnancy complications, and neonatal morbidity. While routine screening often focuses on Chlamydia trachomatis, broader detection is limited by laboratory turnaround times and restricted test panels. Methods We analysed 6003 home-collected urine and/or swab samples submitted for sexual health screening in the UK. Samples were tested in the laboratory for 10 bacterial and viral pathogens. A total of 5859 urine and 1627 swab samples were processed, with paired samples assessed for diagnostic agreement. Results The most common infections detected in urine were Ureaplasma urealyticum (12.1%), Mycoplasma hominis (8.6%), and Chlamydia trachomatis (2.4%). Swabs showed similar prevalence, with Ureaplasma urealyticum (11.6%) most frequent, followed by Mycoplasma hominis (10.4%) and HSV-2 (4.4%). Paired urine–swab samples demonstrated strong agreement, though swabs improved HSV detection. Conclusions Ureaplasma urealyticum was the most prevalent STI detected, yet only Chlamydia trachomatis is routinely screened in England. Comprehensive laboratory testing of home-collected samples could reduce the hidden burden of STIs, infertility, pregnancy complications, and neonatal infections, while offering confidential and accessible diagnostics.
Keywords: STI; STD; chlamydia; gonorrhoea; Confidante®; home sample collection